Updates on the Management of Advanced, Metastatic, and Radioiodine Refractory Differentiated Thyroid Cancer - Tumino, Dario; Frasca, Francesco; Newbold, Kate (Frontiers in Endocrinology, 2017)
Differentiated thyroid cancer (DTC) accounts for 95% of all thyroid cancers and is generally an indolent tumour, treated effectively with surgery, radioactive iodine and TSH suppressive therapy. However, 5-10% of patients have advanced disease, with aero-digestive tract invasion, distant metastases or radio-iodine refractory disease, with poor prognosis. This review focuses on the approaches for treating advanced DTC, including management of gross extra-thyroidal extension, recurrent loco-regional or distant metastatic disease, the role of external beam radiation therapy and systemic treatment. Locally ablative treatment modalities, including surgery, radiation therapy and thermal ablation are evolving and can be used in selected patients. In recent years new therapeutic agents with molecular targets have become available and two multi-kinase inhibitors (MKIs), Sorafenib and Lenvatinib, have been licensed for iodine refractory DTC showing an advantage in terms of progression free survival (PFS), although an impact on overall survival has not been proven yet. Management of advanced thyroid cancer can be challenging but a multi-disciplinary approach can significantly improve outcomes for this patient population.